The relationship between workload and work life balance in generation Z employees - Rachman, Hudan Azkiya; Satwika, Pratista Arya (UIN Maulana Malik Ibrahim Malang, 2024)
In recent years, the world of work has seen the arrival of a new generation known as Generation Z. Generation Z has different desires from previous generations, especially in the aspect of work flexibility related to work life balance. In achieving work life balance, workload analysis is needed, because workload can indirectly lead to a decrease in work life balance. This study aims to determine the relationship of workload to work life balance in Generation Z employees at PT “X”. The research method used is quantitative method using Spearman Rank non-parametric test. The subjects of this study were 61 employees at PT “X” using saturated samples. This study uses a workload scale and a work life balance scale. The results showed a positive relationship between workload and work life balance with a correlation value of 0.352 (p < 0.05). This shows that when the level of workload is increased according to the ability of employees, the level of work life balance also tends to increase, and vice versa. This finding provides important implications for organizations to pay attention to workload so that generation Z employees can achieve their work-life balance. KEY WORDS: workload; work-life balance; employees; generation z